The profile of acute glomerulonephritis among Indonesian children - Husein Albar; Syarifuddin Rauf (Paediatrica Indonesiana, 2005)
Background Acute glomerulonephritis (AGN) is a form of glom-erulonephritis characterized by sudden and explosive onset of glom-erular injury symptom. It usually occurs after recent infection bygroup A beta-hemolytic streptococcus. AGN among Indonesianchildren seems to be less frequently reported than that among othercountries.Objective To determine the current profile of AGN among Indo-nesian children hospitalized in eleven teaching centers.Methods This was a descriptive, cross-sectional study, based ona review of the standard medical records of 509 children with AGNhospitalized in 11 teaching centers in Indonesia over a five-yearperiod (1997-2002). Data extracted from the medical records con-sisted of history of illness, clinical and laboratory findings, and chestX-rays.Results Age of the patients at the onset of AGN ranged from 2.5 to15 years, with peak age of 8.5 years. The majority (76.4%) wasabove 6 years old with male predominance (58.3%). About 68.9%and 82% of the patients came from low socioeconomic and low edu-cational status families. Antecedent upper respiratory infections wereobserved in 45.8% cases and pyoderma in 31.6%. The diseaseseemed to be more commonly elicited by streptococcal infectionthan by other infections, as proved by an elevated anti-streptolisinO (ASO) titer (66.6%) and decreased C 3 concentrations (60.4%).The frequent clinical features included periorbital edema (76.3%),hypertension (61.8%), and gross hematuria (53.6%). The most preva-lent laboratory findings were microhematuria (99.3%), proteinuria(98.5%), raised erythrocyte sedimentation rate (85.3%). The initialchest X-rays showed pleural effusion (81.6%) and cardiomegaly(80.2%), whereas echocardiogram documented pericardial effusion(81.6%). Acute pulmonary edema (11.5%), hypertensive encepha-lopathy (9.2%), and acute renal failure (10.5%) were frequent com-plications noted in our study.Conclusion Despite no adequate data on throat or skin cul-tures, AGN among Indonesian children seems mostly to bepoststreptococcal AGN as proved by the elevated ASO titerand decrease in serum C 3 concentration